Pengembangan Usaha Pengolahan Biji Karet Kepada Masyarakat Pedesaan Di Desa Tanjung Menang - Sari, Novita; Indri Yustika, Retno; Susanti, Eva; Andria Erza, Nia (Indonesian Journal of Dedication and Educations, 2024)
Relatively few farmers use rubber seeds. This is due to the lack of public knowledge regarding the potential of rubber seeds themselves. Rubber seeds tend to be left scattered on plantation land even though the nutritional content of rubber seeds is quite high, especially carbohydrates, proteins and fats which can be used as food. Tanjung Menang Village, South Prabumulih District, Prabumulih City, South Sumatra, Indonesia is one of the villages whose people's main pursuits are rubber plantations. The implementation method used is Asset Based Community Development (ABCD). During the implementation of this PKM, observation, socialization and practice of processing rubber seeds into crackers and dancing packaging were carried out.